3D numerical study on estimating flow and performance parameters of solar updraft tower (SUT) plant: Impact of divergent angle of chimney, ambient temperature, solar flux and turbine efficiency. (20th May 2020) - Das, Pritam; Chandramohan, V.P.
Abstract: A 3D numerical model was made to analyse the effect of divergence angle of chimney ( Φ ch ), ambient temperature ( T a ), solar flux ( I ) and turbine efficiency ( η tur ) on wind flow and performance parameters of a solar updraft tower (SUT). A parametric study was carried out by varying Φ ch from 1 to 5° for different I (600–900 W/m 2 ) and the results were compared with results for existing cylindrical chimney SUT (CC-SUT) plants. The range of T a selected was 293–318 K and η tur was 0.54–0.9%. Five different configurations of divergent chimney SUT (DC-SUT) plants were modelled. It was noticed that at Φ ch of 2°, the average velocity of air at chimney base was enhanced by 58.9% compared to CC-SUT plant. The average absorber plate temperature increased from 316.4 to 332.85 K with an increase in I from 600 to 900 W/m 2 for Φ ch of 2°. The maximum overall efficiency, theoretical and actual power output of the DC-SUT plant were 0.0307%, 3.99 W and 2.67 W, respectively. The exergy of DC-SUT was 58% higher when Φ ch was increased from 1 to 2° at I  = 900 W/m 2 . Correlations were generated to calculate performance parameters as functions of geometrical parameters. Highlights: Five different models of SUT plant were developed with different divergent angle ( Φ ch ). Influence of Φ ch on flow and performance characteristics were studied. Effect of ambient temperature, solar flux and turbine efficiency also investigated. Air velocity, pressure gradient, volume flow rate, power output ( P act ) and efficiency ( η ovl ) were maximum at Φ ch  = 2°. With increase in η tur from 54 to 90%, η ovl and P act improved to 67% and 67.4%, respectively, at Φ ch  = 2°.